Determination of the scope of the experimental-calculation method for measuring the touch voltage - Koliushko, D. G.; Rudenko, S. S.; Saliba, Abdel Nour (Національний технічний університет "Харківський політехнічний інститут", 2023)
The work is devoted to the improvement of methods for determining the normalized parameters of the grounding system (GS) of operating power stations and substations. The aim of the work is determination of the scope of the experimental-calculated method for measuring the touch voltage, depending on short-circuit (SC) current value for the given dimensions of the GS and the type of soil. Methodology. The study analyzed the non-linear effect of the SC current value on the touch voltage, taking into account such factors as the GS size and the soil type. The calculation used statistical data on the GS size and the characteristics of the soil obtained by monitoring the GS state of 585 operating electrical substations with a voltage class of 110-750 kV using the induction method and the method of vertical soil sounding, respectively. For the calculation, a mathematical model of a non-equipotential GS located in a three-layer semiconductor space with plane-parallel boundaries was used, this model was developed using the method of integro-differential equations. Results. To determine the scope of the method, in this work it is proposed to use the linearity criterion, which is determined due to the ratio of the constant of reduced touch voltage to the current value. The example shows the method for determining the threshold minimum and maximum values of the measuring current of the soil, in the range between which the measurements by experimental-calculated methods are impossible. A table of threshold current values has been formed and recommendations have been developed on the possibility of using experimental-measuring methods for determining the touch voltage depending on the GS size and soil characteristics.

Метою роботи є визначення області застосування експериментально-розрахункового методу вимірювання напруги дотику в залежності від значення струму короткого замикання для заданих розмірів заземлювального пристрою (ЗП) та типу ґрунту. В дослідженні було проаналізовано нелінійний вплив величини струму КЗ на напругу дотику з урахуванням таких факторів як розмір ЗП та тип ґрунту. Для розрахунку була використана математична модель нееквіпотенційного ЗП, розташованого у тришаровому напівпровідному просторі з плоско-паралельними границями поділу, що була розроблена за допомогою методу інтегро-диференційних рівнянь. Для визначення області застосування методу в роботі запропоновано використовувати критерій лінійності, який визначається через відношення сталої приведеної напруги дотику до поточного значення. Сформовано таблицю значень порогових струмів та розроблено рекомендації щодо можливості використання експериментально-вимірювальних методів визначення напруги дотику в залежності від розміру ЗП та характеристик ґрунту.
Keywords: electrical substations; grounding system; modeling of the electromagnetic processes; touch voltage; soil characteristics; short-circuit; електрична підстанція; заземлювальний пристрій; моделювання електромагнітних процесів; напруга дотику; характеристики ґрунту; коротке замикання